IMPLEMENTASI PERBAIKAN KUALITAS UNTUK MENGURANGI DEFECT AIRCRAFT PAINTING TOUCH-UP DENGAN METODE DMAIC DI INDUSTRI PENERBANGAN - Fardiansyah, Ismail; Khusyaini, Ahmad; Maulana, Irman; Widodo, Tri (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2025)
In line with technological advancements and increased consumer expectations, quality has become a key factor in the service industry. PT. XYZ, which operates in the aircraft maintenance field, faces the challenge of reducing defects in the aircraft painting touch-up process. This research aims to reduce these defects using the DMAIC method. The DMAIC phases include define, measure, analyze, improve, and control. In the define phase, it was found that dust defects were the most dominant. Initial measurements showed an average DPMO (defects per million opportunities) of 12,129 and a sigma of 3.773. Analysis using the Ishikawa diagram identified the root causes of the problem, and FMEA helped determine the priority root causes that needed immediate improvement. The main causes of the aircraft paint touch-up defects were material cleaning that left fibers on the surface to be painted, and the spray gun being in an un optimized condition for use. Suggested improvements included procuring the appropriate cleaning materials and implementing a preventive maintenance checklist for the spray gun. The implementation of these improvements showed a reduction in dust defects, with the DPMO dropping to 3,477 and sigma increasing to 4.209. These results demonstrate that the improvements made were effective in reducing defects and enhancing painting quality.Keywords: DPMO, sigma, DMAIC, dust defects, aircraft painting.